2020
DOI: 10.3390/cancers12071989
|View full text |Cite
|
Sign up to set email alerts
|

Merkel Cell Polyomavirus T Antigens Induce Merkel Cell-Like Differentiation in GLI1-Expressing Epithelial Cells

Abstract: Merkel cell carcinoma (MCC) is an aggressive skin cancer frequently caused by the Merkel cell polyomavirus (MCPyV). It is still under discussion, in which cells viral integration and MCC development occurs. Recently, we demonstrated that a virus-positive MCC derived from a trichoblastoma, an epithelial neoplasia bearing Merkel cell (MC) differentiation potential. Accordingly, we hypothesized that MC progenitors may represent an origin of MCPyV-positive MCC. To sustain this hypothesis, phenotypic comparison of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 60 publications
5
36
0
Order By: Relevance
“…Therefore, this raft system would be ideal for studying co-factors that collaborate with the MCPyV T antigens to facilitate MCC biogenesis. Gain-of-function studies with transcription factor ATOH1 [ 20 , 26 ] and GLI1 [ 21 ], as well as loss-of-function studies with T antigens [ 28 ], have already provided insight into the potential mechanisms involved in this process. With our model, the biological consequences described in these studies, specifically cell morphology and behavior, can be explored further in a structurally and environmentally relevant model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this raft system would be ideal for studying co-factors that collaborate with the MCPyV T antigens to facilitate MCC biogenesis. Gain-of-function studies with transcription factor ATOH1 [ 20 , 26 ] and GLI1 [ 21 ], as well as loss-of-function studies with T antigens [ 28 ], have already provided insight into the potential mechanisms involved in this process. With our model, the biological consequences described in these studies, specifically cell morphology and behavior, can be explored further in a structurally and environmentally relevant model.…”
Section: Discussionmentioning
confidence: 99%
“…Binding of MCPyV LT to Rb inhibits Rb’s capacity to regulate the activity of the transcription factor E2F, a property that contributes to the transforming capacity of other polyomaviruses [ 18 ]. Multiple investigators have uncovered the transforming/tumorigenic properties of MCPyV ST and/or LT in a variety in vitro and in vivo settings [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Nevertheless, perhaps the strongest evidence for the role of MCPyV ST and LT in the cancer phenotype of MCPyV+ MCC is the observation that silencing their expression induces cell cycle arrest and apoptosis [ 27 ] and causes MCPyV+ MCC cells to undergo phenotypic changes and apparent conversion to a neuron-like cell type [ 28 ], demonstrating the critical role of these viral proteins in MCC.…”
Section: Introductionmentioning
confidence: 99%
“…Merkel cells arise from epidermal progenitor cells [ 77 , 79 ] and ectopic expression of the Merkel cell specification factor atonal homolog 1 (ATOH1) in epithelial cells induces Merkel cell development [ 80 ]. Interestingly, MCPyV LT expression in keratinocytes has been observed to not only increase ATOH1 expression [ 50 ] but also prevent its degradation [ 52 ]. Furthermore, combined expression of the MCPyV T antigens and cellular genes GLI1 or ATOH1 induces Merkel cell-like phenotypes in vitro [ 52 ] and MCC-like lesions in vivo [ 33 ], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, MCPyV LT expression in keratinocytes has been observed to not only increase ATOH1 expression [ 50 ] but also prevent its degradation [ 52 ]. Furthermore, combined expression of the MCPyV T antigens and cellular genes GLI1 or ATOH1 induces Merkel cell-like phenotypes in vitro [ 52 ] and MCC-like lesions in vivo [ 33 ], respectively. A recent study reported sequencing evidence that a MCPyV-positive MCC was derived from an epithelial lineage [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation